Guiding of laser-generated fast electrons by exploiting the resistivity-gradients around a conical guide element. (29th April 2015) - Robinson, A P L; Schmitz, H; Green, J S; Ridgers, C P; Booth, N
Abstract: Previously it has been suggested that the resistivity gradient at the interface between two different Z materials may allow one to guide a laser-generated fast electron beam propagating in a solid density target due to the enhanced growth of resistive self-generation of magnetic field and that this might be employed in an ellipsoidal target to produce a more collimated beam for propagation through homogeneous material. In this paper we show that a low-angle conical element may also have high efficacy in producing a collimated flow. Although the conical element does not have the geometric focussing properties of the ellipsoidal configuration, the conical element will tend to reduce the angular spread of the fast electrons through reducing their propagation angle on each successive bounce